Co-Occurrence Mapping of Disparate Data Sets to Assess Potential Aquaculture Sites in the Gulf of Maine. Issue 1 (2nd January 2018) - Tlusty, Michael F.; Wikgren, Brooke; Lagueux, Kerry; Kite-Powell, Hauke; Jin, Di; Hoagland, Porter; Kenney, Robert D.; Kraus, Scott D.
ABSTRACT: As the need for aquaculture continues to grow, expansion of marine aquaculture into the coastal ocean and beyond will require an understanding of ocean use and attention to spatial planning with engagement from a variety of industry sectors and stakeholders. The easiest means to site aquaculture will be to demonstrate locations that lack of conflict with exiting industries and ecosystem components. Under this framework, the potential space for aquaculture in a 123, 023-km 2 area within the federal waters of the Gulf of Maine was determined by assessing concurrent use by the fishing and shipping industries and also by large pelagic animals (baleen whales and turtles). All three user groups were evaluated for use across seasons, and these data layers were then overlaid to create an index of low use areas that constitute a first pass assessment for where aquaculture would be suitable. The low-use areas (little presence of fishing, shipping and baleen whales and turtles) were focused on Nantucket shoals, and in the central parts of the Gulf of Maine and Georges Bank. A total of 18, 778 km 2, or 15.2%, was identified as low-use areas with the closest being 38 km to shore and the farthest being over 240 km from shore. With 46 km being the current outer limit for aquaculture profitability, then only 5, 978 km 2, or roughly 5%, is available. In order for aquaculture to be able to find more suitable space, it will need to work cooperatively with the existing users to demonstrate where space can be shared as opposed to being relegated to low-use portions of the Gulf of Maine.